HEALTH SEEKING BEHAVIOUR AND PATTERN OF ADHERENCE TO TREATMENT AMONG PATIENTS WITH TYPE-2 DIABETES MELLITUS IN CENTRAL HOSPITAL WARRI, DELTA STATE (2013)
Type-2 Diabetes mellitus (T2DM) could be well managed if patients adhere strictly to treatment regimen. Adherence to treatment (ATT) is a major challenge among patients with T2DM partly because the disease requires lifelong management to prevent the onset of complications. Previous studies on ATT have not been linked with studies on Health Seeking Behaviours (HSBs). Consequently, a study on HSBs and factors influencing ATT of patients with T2DM will be useful for its effective management. This study was therefore designed to investigate HSBs and pattern of ATT among T2DM patients in Central Hospital Warri, Delta State. A cross-sectional study was conducted among 350 purposively selected patients with T2DM. A semi-structured questionnaire was interviewer administered to obtain information on respondents’ socio-demographic characteristics, HSBs, level of ATT, factors influencing ATT and suggestions on ways of improving ATT. A 14-point scale graded; poor (0-8) and good (>8) was used to measure HSBs. A 24-point scale graded; partial (0-13) and strict (>13) was used to measure ATT. Descriptive statistics, Chi-square test and logistic regression were used to analyse the data with level of significance set at 0.05. Mean age of respondents was 57.9 ± 9.8 years, 60.9% were females and 78.0% were married. More than 95.0% exhibited good HSBs and 58.0% adhered strictly to treatment. Analysis of the determinants of non-adherence to treatment showed that taking alternative traditional medicines (herbs) for treatment of the disease was the major contributing variable (OR = 2.5, 95% CI = 4.55-1.69). Factors that hindered adherence included difficulty in sticking to prescribed diets (69.1%) and the least was busy schedule of doctors to listen to patients’ complaints (0.3%). Respondents who were diagnosed with T2DM at mid-adulthood (40-49 years) did not significantly exhibit strict ATT (27.7%) more than those (15.4%) who were diagnosed at late-adulthood (50-59 years). Suggestions on ways of improving ATT included self discipline (46.9%) and encouragement from healthcare personnel (44.0%). Lack of awareness about the disease (42.6%) was a major challenge confronting patients with T2DM. One of the ways of overcoming the challenges of T2DM was creation of awareness as suggested by 39.1% of respondents. Respondents exhibited good health seeking behaviour but use of alternative medicine (herbs) remains a major challenge among patients with type-2 diabetes mellitus. Health education on diabetic care with emphasis on adherence to treatment regimen, among other strategies, should be organised regularly for diabetic patients.